2012
DOI: 10.1111/j.1399-5448.2012.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

A 12-wk follow-up study to evaluate the effects of mixing insulin lispro and insulin glargine in young individuals with type 1 diabetes

Abstract: These data suggest that mixing IL with IG immediately before the SC injection decreases IL serum peak concentration without affecting the glycemic profile after 12 wk in this group with type 1 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Lucchesi and cols. (2012), when evaluating the effects of a treatment that mixed two types of insulin (Lispro and Glargine) did not observe any difference in glycemic variability (28). Similar results were found by Iga and cols.…”
Section: Discussionsupporting
confidence: 75%
“…Lucchesi and cols. (2012), when evaluating the effects of a treatment that mixed two types of insulin (Lispro and Glargine) did not observe any difference in glycemic variability (28). Similar results were found by Iga and cols.…”
Section: Discussionsupporting
confidence: 75%
“…A recent study evaluating the effect of insulin glargine and insulin lispro in patients with diabetes mellitus reported no AEs in patients throughout the study period [40]. Heller et al reported fewer AEs with insulin glargine (4.9%) as compared with insulin detemir (11.7%) among patients with T2DM [41].…”
Section: Discussionmentioning
confidence: 99%